Analysis of the Sustainability of Renewable Energy in Supporting Indonesia's Net Zero Emissions Target by 2060 - Judijanto, Loso (Westscience Press, 2025)
Indonesia’s commitment to achieving net zero emissions by 2060 underscores the pivotal role of renewable energy in ensuring environmental sustainability and energy security. This study analyzes the sustainability of renewable energy systems in Indonesia through a comprehensive literature review and document analysis. It examines the progress, challenges, and opportunities in renewable energy development, highlighting the critical role of policy frameworks, financing mechanisms, technological innovations, and community engagement. The findings reveal that while Indonesia has made significant strides in geothermal and hydropower, systemic barriers such as policy inconsistencies, financial constraints, and infrastructure limitations hinder the transition. Lessons from successful renewable energy transitions in Germany, India, and China provide actionable insights for accelerating Indonesia’s energy transition. Recommendations include strengthening policy coherence, mobilizing green financing, modernizing energy infrastructure, and fostering international collaboration to achieve Indonesia’s ambitious net zero emissions target.